2017
DOI: 10.3390/jmse5010010
|View full text |Cite
|
Sign up to set email alerts
|

Application of State of Art Modeling Techniques to Predict Flooding and Waves for an Exposed Coastal Area

Abstract: Flood Insurance Rate Maps (FIRMs) are developed by the Federal Emergency Management Agency (FEMA) to provide guidance in establishing the risk to structures and infrastructure in the coastal zone from storm surge and coincidental waves. The maps are used by state agencies and municipalities to help guide coastal planning and establish the minimum elevation standard for new or substantially improved structures. A summary of the methods used and results of 2012 FIRM mapping are presented for Charlestown, RI; a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 8 publications
(23 reference statements)
3
20
0
Order By: Relevance
“…The results of the simulations are referred to as the NAST method in the following, referring to a combination of NACCS and STWAVE. [7]. Warwick study area is shown in the red circle.…”
Section: Wave Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the simulations are referred to as the NAST method in the following, referring to a combination of NACCS and STWAVE. [7]. Warwick study area is shown in the red circle.…”
Section: Wave Modelingmentioning
confidence: 99%
“…Manning roughness was specified based on a 30 m resolution map of ground cover, provided by the RI Geographic [7]. Warwick study area is shown in the red circle.…”
Section: Wave Modelingmentioning
confidence: 99%
See 3 more Smart Citations